"Is it time to stop driving?": A randomized clinical trial of an online decision aid for older drivers. Issue 7 (20th April 2022) - Betz, Marian E.; Hill, Linda L.; Fowler, Nicole R.; DiGuiseppi, Carolyn; Han, S. Duke; Johnson, Rachel L.; Meador, Lauren; Omeragic, Faris; Peterson, Ryan A.; Matlock, Daniel D.
Abstract: Background: Many older adults face the difficult decision of when to stop driving. We sought to test whether an online driving decision aid (DDA) would improve decision quality. Methods: This prospective two‐arm randomized trial enrolled English‐speaking licensed drivers (age ≥70 years) without significant cognitive impairment but with ≥1 diagnosis associated with increased likelihood of driving cessation; all participants received primary care in clinics associated with study sites in three states. The intervention was the online Healthwise® DDA for older adults addressing "Is it time to stop driving?"; control was web‐based information for older drivers only. The primary outcome was decision conflict as estimated by the Decisional Conflict Scale (DCS; lower scores indicate higher quality). Secondary outcomes were knowledge and decision self‐efficacy about driving decisions. We examined postrandomization differences in primary and secondary outcomes by study arm using generalized linear mixed‐effects models with adjustment for site and prerandomization scores. Results: Among 301 participants (mean age: 77.1 years), 51.2% identified as female and the majority as non‐Hispanic (99.0%) and white (95.3%); 98.0% lived in an urban area. Participant characteristics were similar by study arm but differed across sites. Intervention participants had a lower mean DCS score (12.3 DDA vs 15.2 control; adjusted mean ratio [AMR] 0.76, 95%CI 0.61–0.95; p  = 0.017). Intervention participants had higher mean knowledge scores (88.9 DDA vs. 79.9 control; OR 1.13, 95%CI 1.01–1.27, p  = 0.038); there was no difference between groups in self‐efficacy scores. The DDA had high acceptability; 86.9% of those who viewed it said they would recommend it to others in similar situations. Conclusions: The online Healthwise® DDA decreased decision conflict and increased knowledge in this sample of English‐speaking, older adults without significant cognitive impairment, although most chose to continue driving. Use of such resources in clinical or community settings may support older adults as they transition from driving to other forms of mobility. Trial registration: ClinicalTrials.gov identifier "Advancing Understanding of Transportation Options (AUTO)" NCT04141891.